Successful headship leadership in primary schools in Cyprus - Angelidou, Kakia (2010)
This research explored the nature and conduct of successful leadership in the context of Cyprus; how policy and school contexts and heads' experience influence headship leadership. The empirical findings of this study draw upon ethnographic methods rooted within the naturalistic paradigm in order to illuminate the complex and dynamic nature of headship leadership in a specific country context. A group often successful heads in urban primary schools of Cyprus was selected. Data was collected through observations, a review of a number of schools' documents and semi-structured interviews carried out with each of the successful heads and with people that had everyday conduct with them.